Neuroscience of Human Attachment - Harald G (Frontiers Research Topics, 2017)
Attachment is a biologically emotion regulation based system guiding cognitive and emotional processes with respect to intimate and significant relationships. Secure relationships promote infants' exploration of the world and expand their mastery of the environment. Adverse attachment experiences like, maltreatment, loss, and separation have long been known to have enduring unfavorable effects on human mental health. Research on the neurobiological basis of attachment started with animal studies focusing on emotional deprivation and its behavioral, molecular and endocrine consequences. The present book presents an interdisciplinary synthesis of existing knowledge and new perspectives on the human neuroscience of attachment, showing the tremendous development of this field. The following chapters include innovative studies that are representative of the broad spectrum of current approaches. These involve both differing neurobiological types of substrates using measures like fMRI, EEG, psychophysiology, endocrine parameters, and genetic polymorphisms, as well as psychometric approaches to classify attachment patterns in individuals. The findings we have acquired in the meanwhile on the neural substrates of attachment in healthy subjects lay the foundation of studies with clinical groups. The final section of the book addresses evidence on changes in the functioning of these neural substrates in psychopathology.